Islamic Political Thought and The Crisis of Global Governance: Towards a Non-Western Theory of Order - Karingayi, Thaha Hamdan (International Journal of Islamic Khazanah, 2025)
Contemporary global politics is increasingly marked by rising geopolitical tensions, fragile institutions, deepening inequality, and declining trust in international systems. Traditional Western models of governance, rooted in sovereignty and liberal internationalism, often fall short in responding to these challenges. This paper rethinks the global order through Islamic political thought, offering insights toward a more inclusive and resilient future. Islamic concepts provide distinctive perspectives on order, justice, and collective responsibility that move beyond the nation-state. Tawhid emphasizes the unity of God and the interconnectedness of creation, grounding universal ethics and accountability. Khilafah/Istikhlaf frames humanity as stewards entrusted with protecting the earth and safeguarding future generations. Maslaha (public interest) and Maqasid al-Shari’ah (higher objectives of Islamic law) operate as flexible tools to promote welfare. Shura (consultative governance) strengthens dialogue and legitimacy across borders, while the Ummah (moral community) inspires transnational solidarity. At the heart of these principles, Adl (justice) remains the foundation of any fair and legitimate system. This study employs a qualitative approach based on secondary literature, drawing from classical texts and contemporary scholarship. Findings reveal that Islamic ideas reframe sovereignty as responsibility, root legitimacy in justice, and offer ethical tools to address structural weaknesses in global governance. Far from advocating theocracy, the paper highlights Islamic thought as a resource for building a pluralistic global order and strengthening dialogue across civilizations.